2013
DOI: 10.3748/wjg.v19.i24.3872
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of radiofrequency ablation in combination with transarterial chemoembolization for hepatocellular carcinoma

Abstract: The combination of RFA with TACE has advantages in improving overall survival rate, and provides better prognosis for patients with intermediate- and large-size HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(100 citation statements)
references
References 0 publications
9
88
0
2
Order By: Relevance
“…38 However, the common procedure-related complications of the combined therapy such as hepatic infarction, biloma, abscess and hepatic arterial bleeding, reported by others, 27,31,34,39 did not occur in our study. In our study, posttreatment syndrome and transient increase in liver enzymes slightly were observed in all patients within 1 week after the treatment, which were comparable with those reported in other studies [8][9][10][11] ; these symptoms were usually self-limited and reversible without special treatment. Interestingly, an increase levels of serum creatinine and urea nitrogen slightly, indicating the renal function impaired, was observed in 7 patients (8.1%) at 1-5 days after the combined treatment.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…38 However, the common procedure-related complications of the combined therapy such as hepatic infarction, biloma, abscess and hepatic arterial bleeding, reported by others, 27,31,34,39 did not occur in our study. In our study, posttreatment syndrome and transient increase in liver enzymes slightly were observed in all patients within 1 week after the treatment, which were comparable with those reported in other studies [8][9][10][11] ; these symptoms were usually self-limited and reversible without special treatment. Interestingly, an increase levels of serum creatinine and urea nitrogen slightly, indicating the renal function impaired, was observed in 7 patients (8.1%) at 1-5 days after the combined treatment.…”
Section: Discussionsupporting
confidence: 80%
“…Currently, the combined TACE and RFA in single-session has rarely been performed in the treatment large HCC, 13 because of concerning about the risk of complications such as hepatic arterial bleeding and hepatic dysfunction. 9,20 Theoretically, the rate of complications should be higher in the combined TACE and RFA than that of TACE or RFA monotherapy. 38 However, the common procedure-related complications of the combined therapy such as hepatic infarction, biloma, abscess and hepatic arterial bleeding, reported by others, 27,31,34,39 did not occur in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Die Relevanz von lebereigenen Stammzellen wird noch untersucht. In jedem Fall ist das proinflammatorische Mikromilieu bei Hepatitis von Bedeutung, welches häufig durch eine autokrine Aktivierung von Interleukin-6 (IL-6) und NFκB-abhängigen Signalen bestimmt wird [46]. Abhängig von der Entzündung und der zugrunde liegenden ätiologischen Faktoren kommt es zu spezifischen Veränderun-gen im Tumorgenom, die sich anhand der jeweiligen Stadien der Progression bzw.…”
Section: » Die Maligne Transformation Ist Abhängig Von Wachstumsfaktounclassified
“…A recent meta-analysis reported that the combination of RFA and TACE has advantages in improving the overall survival rate for patients with intermediate and large-sized HCCs, compared to RFA monotherapy [71]. These synergistic effects may be due to the decreased blood flow into the target lesions with the additional elimination of adjacent micrometastasis.…”
Section: Advances In Combined Treatment With Tumor Ablationmentioning
confidence: 99%